2018
DOI: 10.4066/biomedicalresearch.29-18-1064
|View full text |Cite
|
Sign up to set email alerts
|

The barriers of clinical education in nursing: A systematic review

Abstract: Considering the great significance of proper clinical education in training nurses qualifying for provision of quality care, this study has been conducted with the aim of investigating the obstacles against clinical education among the nurses. In this systematic review study, international databases (PubMed, Web of Science, Scopus, CINHAL, EMBASE, ERIC, Google scholar, as well as national banks including Magiran and SID) were searched from the time of inception until January 30, 2018. The obstacles of clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 30 publications
0
17
0
1
Order By: Relevance
“…[ 29 ] In a study, discrimination between nursing students and other students in the field of medical sciences, as well as the reluctance of staff to collaborate with nursing educators, have been suggested as supportive barriers for students. [ 30 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 29 ] In a study, discrimination between nursing students and other students in the field of medical sciences, as well as the reluctance of staff to collaborate with nursing educators, have been suggested as supportive barriers for students. [ 30 ]…”
Section: Resultsmentioning
confidence: 99%
“…An extensive training, however, may not be possible from a logistical perspective, especially if these measurement instruments to be implemented and used national wide [ 38 ]. Thus, developing an instrument that is simple and can meet the caregivers’ level of oral health knowledge and skills could be an alternative approach that may establish sufficient reliability without the need for prior training.…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicated the peak medical dominance and physician-centered atmosphere in clinical education due to the presence of physicians managing all clinical centers, so most clinical resources and facilities were available to them and nursing students were not allowed to use them. Numerous studies have confirmed severe discrimination between nursing and medical students in terms of distribution of welfare and educational facilities, including libraries, the Internet, and training classes (6,18,29). Asirifi (2017) reported in a study in Ghana that students must purchase their own equipment such as a thermometer, gloves, a stethoscope, and hand towels for clinical learning (30).…”
Section: Physician-centered University Educationmentioning
confidence: 99%